USING MIND MAPPING TO IMPROVE STUDENT’S WRITING SKILLS OF THE ELEVEN GRADES AT SMP PRAJA MUDA ACADEMIC YEAR 2022/2023 - Dewi Sari Mulia (Edelweiss : Journal Of Innovation In Educational Research, 2023)
The aim of this study is to investigate the use of mind mapping as a tool to improve the writing skillsof students in Yaspen Nurul Huda Serapuh ABC 2023. Four students with writing difficultiesparticipated in the study. In the study, researchers used observational techniques to determine students’writing abilities through mind mapping. Teacher performed descriptive analyzes of students’ writingtest scores before and after they applied the ”mind mapping” technique in their writing. The purposeof this study was also to determine the effectiveness of mind mapping in teaching writing. The resultsof this study provide insight into the effectiveness of using mind mapping in writing classes in theseschools to improve students writing skills.